2018
DOI: 10.1021/acs.jafc.8b04514
|View full text |Cite
|
Sign up to set email alerts
|

Ginkgolide A Prevents the Amyloid-β-Induced Depolarization of Cortical Neurons

Abstract: Utilizing the N-methyl-D-aspartate (NMDA) receptor antagonist as a strategy, memantine is the only agent available for clinically treating mild to severe Alzheimer's disease (AD). Our aim was to develop novel similar herb-based drugs. Using a screening platform, ginkgolide A (GA), a pure compound extracted from Ginkgo biloba, was found to attenuate amyloid β (Aβ)-induced abnormal depolarization in mouse primary cortical neurons. Using receptor agonists, it was determined that GA inhibits both NMDA receptors an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…Previous studies have shown that EGb is effective in the prevention and treatment of aging-related diseases [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that EGb is effective in the prevention and treatment of aging-related diseases [12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…EGb preparation is a relatively successful case of plant medicine developed by modern science and technology and occupies an important position in the field of antiaging and clinical medication for cardiovascular and cerebrovascular diseases [ 9 , 11 ]. Previous studies have shown that EGb has certain efficacy in the prevention and treatment of age-related diseases [ 9 , 12 14 ]. However, the pharmacologic profiles of EGB for aging remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The results were shown in Additional le 1: Chemical information of main compounds in EGb. The OB of ginkgolide A was < 30%, but it was a common compound in EGb and shown to have effects on prevention and treatment of Alzheimer's disease (AD), a disease associated with aging [23,24]. Hence, ginkgolide A was also considered to be a candidate compound.…”
Section: Identifcation Of the Active Compounds In Egbmentioning
confidence: 99%
“…EGb preparation is a relatively successful case of plant medicine developed by modern science and technology, and occupies an important position in the eld of anti-aging and clinical medication for cardiovascular and cerebrovascular diseases [9,11]. Previous studies have shown that EGb has certain e cacy in the prevention and treatment of age-related diseases [9,[12][13][14]. However, its pharmacologic pro les of EGB for aging remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Ginkgo biloba is also considered as a neuroprotective agent. Ginkgolide A inhibits Aβ-induced neuronal degradation via JNK phosphorylation and NMDA/AMPA-induced depolarization, thus suppress the activity of plaque [43]. EGb 761 increases the neurogenesis in the adult hippocampus region and CREB phosphorylation in the transgenic mouse model of AD [44].…”
Section: Alzheimer's Disease and Related Dementiasmentioning
confidence: 99%